Medical Rehabilitation in Patient with Post ORIF et causa Neglected Epiphyseal Fracture Distal Radius-Ulna Sinistra: A Case Report - Christina A. Damopolii; Joudy Gessal; Jonathan P. Suyono (Universitas Sam Ratulangi, 2023)
Distal radius-ulna fracture is one of the most common human osseous injuries, with incidence rate increasing worldwide. There are two peaks of prevalence: the first around the 10th and the second around the 60th year of life. During childhood, they are among the most common pediatric fractures accounting for 19.9 to 35.8% of all pediatric fractures. We reported a case of a boy 13 years old diagnosed as post open reduction internal fixation distal radius ulna et causa epiphyseal fracture. He came to rehabilitation outpatient clinic with chief complaint pain on his left forearm. He underwent a surgery two weeks ago at the distal radius ulna. The surgeon did osteotomy on ulna and then fixated with plate and screw. On physical examination, there were pain and range of motion limitation mainly on the forearm and wrist joint. The patient was treated with low level laser therapy at the surgical wound to promote healing and decrease edema, initial digital motion exercise along with active range of motion of the uninvolved joints. He was also educated about icing and medicamentation if pain still persisted. Once adequate bony healing had occurred, active, active-assisted, progressive passive wrist motion, and strengthening exercise using resistance were performed to maximize the result. At the end of rehabilitation program, there was great improvement on pain and also range of motion improvement. Albeit, there was still a slight range of motion limitation on ulnar deviation and wrist extension by 5 degrees. In conclusion, rehabilitation program is very beneficial in treating post-surgery patient using modalities and exercises to improve functional function. Keywords: epiphyseal fracture; radius-ulna; medical rehabilitation